Revisiting the Information Motivation Behavioral Skills Model in Antiretroviral Therapy Adherence: A Systematic Review of Mechanisms, Contextual Barriers, and Policy Implications in HIV Care - Darlis, Idhar; Arsin, A. Arsunan; Riskiyani, Shanti (International Journal of Statistics in Medical Research, 2026)
Antiretroviral therapy (ART) adherence remains essential for viral suppression, prevention of drug resistance, and improved long-term outcomes among people living with HIV. This systematic review examined how the Information–Motivation–Behavioral Skills (IMB) model explains ART adherence, how its constructs interact, and how contextual barriers influence intervention effectiveness. PubMed, ProQuest, and Google Scholar were searched for peer-reviewed studies published between 2019 and 2024 in accordance with PRISMA 2020 guidelines. Nineteen studies were included, comprising randomized controlled trials, quasi-experimental studies, cross-sectional analyses, mixed-methods studies, structural equation modeling, and developmental research, and were synthesized narratively because of substantial clinical and methodological heterogeneity. Across studies, information and motivation were associated with adherence-related outcomes, but behavioral skills, particularly self-efficacy, problem-solving, communication, and medication-management ability, emerged as the most consistent proximal mechanism linking these constructs to adherence. Psychosocial and structural barriers, including stigma, depression, substance use, limited social support, and health-system constraints, weakened these pathways when not directly addressed. The findings support an integrated, context-sensitive application of the IMB model combining education, motivational support, practical skill development, and structural interventions. Further longitudinal and randomized studies using standardized, objective adherence measures are needed to strengthen causal inference and guide scalable HIV programs and policy.